Cyclodextrin-poly(ε-caprolactone) based nanoparticles able to complex phenolphthalein and adamantyl carboxylate - Ailincai, Daniela; Ritter, Helmut (Beilstein Journal of Nanotechnology, 2014)
A new compound composed of poly(ε-caprolactone) and β-cyclodextrin (β-CD) was synthesized by click chemistry. This compound was used to obtain stable nanoparticles, which have been proven to be able to complex phenolphthalein and adamantyl carboxylate. The nanoparticles are characterized by a distinct morphology, i.e., a hydrophobic core formed by the polyester chain and a shell containing the CD part. Moreover, the formed nanoparticles have been proven to encapsulate umbelliferone in the polyester phase, which may serve as an example for the uptake of a drug. The formed nanoparticles were characterized in terms of sizes and morphology by both DLS and TEM.
Keywords: click reaction; complexation; cyclodextrin; encapsulation; nanoparticles